2021
DOI: 10.14808/sci.plena.2021.091501
|View full text |Cite
|
Sign up to set email alerts
|

A novel Thermothelomyces heterothallicus PA2S4T fungus isolated from the soil induces chitinase production using orange peel flour

Abstract: Chitinases are enzymes capable of hydrolysing the β-1,4 bonds of chitin releasing chitooligosaccharides and N-acetylglucosamine and are widely used in food, pharmaceutical, and agricultural industries. Microorganisms are potential producers of this enzyme; however, there are no reports in the literature on the production of chitinase by fungi of the genus Thermothelomyces. Thus, this work aimed to investigate the production of extracellular chitinase using alternative carbon sources by the fungus isolated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
(46 reference statements)
1
5
0
Order By: Relevance
“…The same bacterial species isolated in this study were used in that study: S. marcescens, P. aeruginosa, and B. cereus. Here, S. marcescens stands out, corroborating the work of Pommer et al [41], a study on the enzymatic hydrolysis of chitin, in which it was among the most promising bacteria in producing chitinase. Those authors found that a combination of enzymes from a filamentous fungus and S. marcescens could completely degrade high concentrations of chitin.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The same bacterial species isolated in this study were used in that study: S. marcescens, P. aeruginosa, and B. cereus. Here, S. marcescens stands out, corroborating the work of Pommer et al [41], a study on the enzymatic hydrolysis of chitin, in which it was among the most promising bacteria in producing chitinase. Those authors found that a combination of enzymes from a filamentous fungus and S. marcescens could completely degrade high concentrations of chitin.…”
Section: Discussionsupporting
confidence: 89%
“…The cells were observed under an optical microscope (40×), and 4000 cells per treatment were analyzed to evaluate all mitotic stages (interphase, prophase, metaphase, anaphase, and telophase). The mitotic index (MI) was calculated using the following equation [41]:…”
Section: Assessment Of Toxicity In a Plant Model (Allium Cepa)mentioning
confidence: 99%
“…The best chitinolytic activity for the enzymes produced by A. terreus, Trichoderma viride AUMC 13021 and Thermothelomyces heterothalicus PA2S4T was found at pH 5.6, 6.5 and 4.5, respectively [24,25,36]. Considering pH stability, the A. niveus chitinase remained more stable than the other fungal chitinases such as that produced by the A. terreus enzyme, which kept 80% of its initial activity when maintained at a pH range from 5.0 to 8.0 for 1 h [24].…”
Section: Discussionmentioning
confidence: 99%
“…Although the production of chitinases by yeasts such as Saccharomyces cerevisiae (ABDEL-KAREEM; RASMEY; ZOHRI, 2019) and Candida albicans (SELVAGGINI et al, 2004) has already been reported, filamentous fungi are those most used in the production of these enzymes; some of the genera used are Trichoderma (BALDONI et al, 2020;LOC et al, 2020), Penicillium (XIE et al, 2021), Aspergillus (ABDEL WAHAB et al, 2022), Metarhizium (DOS REIS et al, 2018), Beauveria (SCHMALTZ et al, 2021 and Thermothelomyces (POMMER et al, 2021).…”
Section: Production Of Fungal Chitinasesmentioning
confidence: 99%
“…Biotechnology industries already use a wide variety of enzymes; fungi, especially filamentous fungi, play a prominent role in the production of these molecules (POMMER et al, 2021).…”
Section: Introductionmentioning
confidence: 99%